Structure of the genes encoding transcription factor IIB and TATA box-binding protein from Drosophila melanogaster. - Lira-De Vito, L.M.; Burke, T.W.; Kadonaga, J.T. (Gene, 1995)
To investigate the structure and regulation of the genes encoding components of the basal RNA polymerase II transcriptional machinery, the Drosophila melanogaster genes encoding transcription factor IIB (TFIIB) and the TATA-box-binding protein (TBP) were isolated and characterized. In the TBP gene, a single intron bisects the sequences that encode the two repeated DNA-binding domains of TBP, which supports the notion that TBP evolved from an earlier form that possessed only a single domain. The transcription start points (tsp) were determined, and there was a good correlation between the tsp that were used in vivo and transcription reactions in vitro. The TFIIB and TBP genes have several similar features, which include high A + T content (68 to 74%) upstream from the tsp, multiple copies of an ATTATTATT sequence motif in the proximal promoter region, the absence of a consensus TATA-box element, and small introns (55 to 64 nucleotides). These genes should be useful in the combined genetic and biochemical analysis of TFIIB and TBP in D. melanogaster.